Pengaruh Pretest Dan Posttest Terhadap Motivasi Belajar Sosiologi Pada Siswa Kelas XI IPS Di UPT SMA Negeri 2 Jeneponto - Yulianti Yulianti; Ridwan Said Ahmad; Supriadi Torro (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine 1) The effect of the pretest on students' learning motivation in the sociology subject class XI IPS at UPT SMA Negeri 2 Jeneponto. 2) The influence of the posttest on students' learning motivation in the sociology subject class XI IPS at UPT SMA Negeri 2 Jeneponto. 3) The influence of the pretest and posttest together on students' learning motivation in the sociology subject class XI IPS at UPT SMA Negeri 2 Jeneponto. This type of research is quantitative research using a descriptive approach, the population in this study was 154 people. The sample size was determined using the Slovin formula, using simple random sampling techniques, samples were taken from a total population of 25% of 154 students, namely 40 respondents. Data collection was carried out using questionnaires and documentation. The validity test uses the bivariate human correlation technique and the reliability test uses the Cronbach's alpha technique. The data analysis technique used is descriptive statistics and inferential statistical analysis using IBM SPSS 25 for Windows. The results of this research show 1) The influence of the pretest on students' sociology learning motivation, obtained a correlation of 0.757, indicating that the relationship between the pretest and students' sociology learning motivation is in the medium category and has a positive direction. 2) The influence of the posttest on learning motivation obtained a correlation of 0.666, which shows that the relationship between the posttest and students' sociological learning motivation is in the medium category and has a positive relationship direction. 3) The influence of the pretest and posttest on student learning motivation where the correlation coefficient value is 0.760. It is in the medium category and has a positive relationship.